Simulation of Depletion-induced Surface Subsidence in a Coal Seam - Chamani, A.; Rasouli, Vamegh (APCBM, 2011)
Coalbed methane (CBM) drew increasingly the attention as an unconventional source of natural gas during the last decades, globally and domestically. In spite of the fact that it is one of the main hazardous concerns in coal mining it is one of the most advantageous sources of natural gas especially due to its high purity of methane and quality. In conventional natural gas reservoirs the pressurized gas is stored in porous space or fracture space but in CBM natural gas molecules mainly is adsorbed to coal matrix. Therefore in contrast to conventional natural gas reservoirs, the gas production of CBM initiates after decreasing the reservoir pressure down to a threshold in order to initiation the desorption process. According to the presence of water in CBMs which creates a remarkable pressure due to hydrostatic head of water the above desorption threshold will be achieved after dewatering process. Dewatering process will lead in decreasing reservoir pressure in one hand which helps the gas desorption but will lead in increasing effective stress which is applied to rock solid skeleton on the other hand. Such an increase in effective stress accounts for rock structure deformation which has a high impact on surface subsidence due to shallow depth of coal seams. Presence of soft formations in dewatered horizon especially coal seams will increase effectively the deformation of the formations, which could potentially result in remarkable subsidence profile.Studying the depletion induced deformation due to CBM production is the main aim of this study. A three-dimensional finite element program developed will be used to investigate the stress field perturbation and rock structure deformation with emphasize on surface subsidence. In order to cover a wide range of real condition in CBM production a sensitivity analysis is carried out on main parameters including coal seam thickness and deformability properties.